Aprehensi Komunikasi dan Kemampuan Menjalin Hubungan Akrab Mahasiswa Baru - Solihat, Manap (Jurnal Soshum Insentif, 2024)
The purpose of this study was to determine the form of anxiety that occurs in new students of the Communication Science Study Program at Unikom and the ability of new students to establish familiarity with other students. The method used is a descriptive qualitative approach method, 12 informants. Individuals who have communication apprehension tend to be more withdrawn and rarely express their opinions in discussions because they admit to being insecure. Not a few new students admit to having communication anxiety when attending lectures. Communication anxiety appears when making presentations, answering questions, asking lecturers, and having ordinary conversations. Having communication anxiety hinders students from developing, requiring a period of adaptation to lectures. The results of this study recommend that advisors or counselors analyze student behavior and create strategies so that anxiety that occurs in new students is reduced, supporting the success of students in the lecture process.